The English Translation of Chinese Political Discourse from a Materialistic Dialectics Perspective - Guigui Jiang; Xu Zhou (Journal of Linguistics and Communication Studies, 2024)
China has witnessed two rounds of large-scale translation activity over the past 40 years of reform and opening-up since 1978. And the focus of the Chinese translation community now has been shifting from “translating the world” to “translating China” after China entered the new era in 2012. Therefore, it is imperative to quicken the pace in China’s “going global” by narrating Chinese stories to the wider world. As an integral part of its global communication, Chinese political discourse represents national attitudes, stances and values. In this regard, how to improve the quality and communication effect of its translation becomes a major problem for China’s translators and global communicators. This paper lends insights into the essential role of material dialectics in its English translation from five aspects, by selecting and analyzing some important official texts and remarks in recent years, so as to provide valuable inspiration for how to better the translation of the field.